Sur les invariants d’espace des linéars d’appuis - Šinkūnas, J. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Ю. Шинкунас. О дифференциальных инвариантах пространства опорных линеаров J. Šinkūnas. Apie atraminių linearų erdvės diferencialinius invariantus